2009
DOI: 10.1097/smj.0b013e3181a2e33e
|View full text |Cite
|
Sign up to set email alerts
|

Toe Hair-Thread Tourniquet Syndrome

Abstract: A 5-month-old boy presented with swelling and discoloration of the right third toe because of hair-thread tourniquet syndrome. This was treated by urgent surgical release of the constricting band, with a successful outcome. The authors stress the importance of recognizing this rare condition and of prompt, complete, surgical release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In the majority of cases, toe HTTS happens accidentally (3) while dressing the baby or removing clothes or with the baby’s repetitive digital movements within the hair hidden in socks or loose fabric of clothing, although in certain circumstances, the possibility of child abuse should be considered (1,4). Ethnic and superstitious motivations may also be involved (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of cases, toe HTTS happens accidentally (3) while dressing the baby or removing clothes or with the baby’s repetitive digital movements within the hair hidden in socks or loose fabric of clothing, although in certain circumstances, the possibility of child abuse should be considered (1,4). Ethnic and superstitious motivations may also be involved (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is based on prompt removal of the constricting fiber (1–5), which sometimes may be undetectable with direct vision because it can be buried by skin reepithelialization (1). After removal, reevaluation is recommended to confirm complete resolution of strangulation (1).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate treatment of hair-thread tourniquet syndrome is urgent removal of the fiber which causes to obstruction (13). Treatment may not always be easy; it may be difficult to see and remove hair or thread, because it may be embedded in the tissue because of edema and epithelial tissue may have covered it after a long time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hair tourniquet syndrome may be successfully treated by using depilatory (15). Topical or systemic antibiotic is generally used after operation (11,13,14).…”
Section: Discussionmentioning
confidence: 99%